Teachers’ knowledge dynamics and innovation in education – Part I. - Révai, Nóra (Neveléstudomány | Oktatás – Kutatás – Innováció, 2017)
Teachers’ knowledge is dynamic; it is constantly shaped by new information, collaboration with colleagues, engagement with teaching tools and textbooks, teaching practice in the classroom, and so on. The paper investigates how knowledge dynamics can be described, building on work conducted in the Innovative Teaching for Effective Learning (ITEL) project of the OECD. A review of literature is conducted through three analytical foci – the individual, social and socio-material – in order to explore processes underlying the dynamics of knowledge functions, structures and the emergence of knowledge. This first part of the paper looks at the individual and social perspectives. Data from the ITEL pilot study is used to illustrate some of these mechanisms. The second part will look at the socio-material perspective and, integrate the three analytical angles into a complexity view of knowledge dynamics and innovation, ultimately highlighting the different ways in which innovation in education is linked to the dynamics of professional knowledge.